PROSPECTS OF APPLYING DATA SCIENCE TO EDUCATION IN THE CONDITIONS OF UZBEKISTAN - Nazirkulov Jamaldin o‘g‘li; Bohodirov Daniyor O'tkirbekovich (Western European Studies, 2024)
This article examines the prospects of applying Data Science technologies in the field of education in the conditions of Uzbekistan. Issues such as necessary infrastructure, training of qualified personnel, data collection and management were discussed for the successful implementation of Data Science in the conditions of Uzbekistan. The measures presented in the article are expected to bring the educational system of Uzbekistan to a new level and help increase the country's competitiveness.
Keywords: Data Science; information analysis; individual teaching